2020
DOI: 10.1016/j.onehlt.2020.100149
|View full text |Cite
|
Sign up to set email alerts
|

The mysterious illness that drove them to their knees - Ah, that Legionnaires’ disease – A historical reflection of the work in Legionnaires’ disease in New Zealand (1978 to mid-1990s) and the ‘One Health’ paradigm

Abstract: And so, formed the basis for the song Legionnaires’ disease (LD) composed by the legendry musician Bob Dylan shortly after this mysterious illness dramatically entered the clinical and epidemiological scene in July 1976 at an American hotel. Now more than forty years have passed since Legionella pneumophila , the causative agent of LD, was formally identified in 1977. Once the publicity associated with the outbreak subsided, there was the challenge to science and health professionals of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Infections obtain their names from the events after which they were described. The identification of Legionnaires' disease was preceded by a conference of American veterans from the Second World War, the so-called Legionnaire, in 1976, which, as it turned out, became the source of a previously unknown disease [37]; the tragedy was blamed on the ventilation and air conditioning system of a luxury hotel in Philadelphia. Participants of the gathering fell ill and suffered from pneumonia, and there were also fatalities.…”
Section: History Of Legionellosismentioning
confidence: 99%
See 1 more Smart Citation
“…Infections obtain their names from the events after which they were described. The identification of Legionnaires' disease was preceded by a conference of American veterans from the Second World War, the so-called Legionnaire, in 1976, which, as it turned out, became the source of a previously unknown disease [37]; the tragedy was blamed on the ventilation and air conditioning system of a luxury hotel in Philadelphia. Participants of the gathering fell ill and suffered from pneumonia, and there were also fatalities.…”
Section: History Of Legionellosismentioning
confidence: 99%
“…A weaker form of the disease in Pontiac could indicate a low infectious dose, but the infection rate among healthcare workers was 95%. This high infection rate suggested that the pathogen was spread through the air [3,37,41].…”
Section: History Of Legionellosismentioning
confidence: 99%
“…They may also occur in soil, compost, or in decaying bark and sawdust. A special case is Legionella longbeachae, rarely found in water samples, but frequently occurring in garden soil [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Disease surveillance for legionellosis began in New Zealand (Aotearoa) in 1979 with the collection of laboratory-based data (cases positive for Legionella species); additional data were available starting in June 1980, when the disease became notifiable ( 5 ). A review of national surveillance data for 1979‒2009 showed that the annual incidence rate for laboratory-identified cases was 2.5 cases/100,000 persons and 1.4 cases/100,000 persons for notified cases ( 6 ); the disparity was caused by not all laboratory-identified cases being notified.…”
mentioning
confidence: 99%